Candida albicans adhesion on reinforced polymethylmethacrylate denture resin: effect of fibre architecture and exposure to saliva - EVREN, BUKET; KADİR, TANJU; ÖZKAN, YASEMİN (WILEY, 2014)
Background and objectives: Fiber-reinforced composites (FRC) are used to reinforce the prosthetic and restorative appliances. This may result in the exposure of the FRCs which may affect the adherence of microorganisms. This study evaluated the adhesion of Candida albicans to a denture base resin (N = 48), reinforced with E-glass FRCs with different architectures [unidirectional (n = 16) and woven (n = 16)], when exposed to either saliva or distilled water. Materials and methods: Specimens without FRC reinforcement served as control (n = 16). After fiber surfaces were exposed, half of the specimens (n = 8/per group) were treated with saliva, the other half was stored in distilled water prior to C. albicans adhesion. The adhered microorganisms were counted under an optical microscope and the data were analyzed. Results: When exposed to distilled water or saliva, specimens with unidirectional (5403.4 cells/cm(2) and 5013.4 cells/cm(2), respectively) (p = 0.202), woven fibers (4053.5 cells/cm(2) and 3726.6 cells/cm(2), respectively) (p = 0.283) and specimens without fibers (2250 cells/cm(2) and 2006.8 cells/cm(2), respectively) (p = 0.423) showed C. albicans adhesion, being not significant. In general, all the specimens exposed to saliva showed 3582.2 cells/cm(2) C. albicans adhesion, while specimens exposed to distilled water showed 3902 cells/cm(2) C. albicans adhesion, yet being not significant (p = 0.436). Regarding fiber type, C. albicans adhesion was significantly affected by the exposed FRC architecture with more favorable results for woven fibers (p < 0.001). Conclusion: Polymethylmethacrylate without FRCs collected less C. albicans. The presence of saliva seems to reduce the adhesion.
Keywords: Acrylic resin; Candida; Saliva; DIFFERENT SURFACE FINISHES; RESILIENT LINER MATERIALS; FIXED PARTIAL DENTURES; WOVEN GLASS-FIBERS; STREPTOCOCCUS-MUTANS; FLEXURAL PROPERTIES; BASE MATERIALS; PLAQUE-FORMATION; IN-VITRO; ADHERENCE